The Quality of State-Property Reporting: Determinants and Intervening Role of Optimization Management in Indonesia Regional Case - Anisykurlillah, Indah; Oktaviana, Anggita (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study examines the effect of legal audit, internal control system, IT utilization, and internal auditors' role as determinants of the quality of state-property reporting intervened by management optimization. The population is the Tegal Regional employee, who manages state-property, including users, regulators, and keepers in 36 regional offices. This case reflects the management and reporting of state-property in the Indonesia regional. Seventy-six respondents were sampled to answer the research instrument and analyzed it by path analysis. The results show that the internal control system, IT utilization, and state property management optimization positively affect state-property reporting quality. The use of internal control systems and IT utilization positively influence the optimization of state-property management. The results also prove that management optimization mediates the internal control system and IT utilization on state-property reporting quality. Contrary evidence that management optimization does not mediate the impact of legal audits and internal auditors' role on the state property report's quality.